2004
DOI: 10.1172/jci200420921
|View full text |Cite
|
Sign up to set email alerts
|

The renal papilla is a niche for adult kidney stem cells

Abstract: Many adult organs contain stem cells, which are pluripotent and are involved in organ maintenance and repair after injury. In situ, these cells often have a low cycling rate and locate in specialized regions (niches). To detect such cells in the kidney, we administered a pulse of the nucleotide bromodeoxyuridine (BrdU) to rat and mouse pups and, after a long (more than 2-month) chase, examined whether the kidney contained a population of low-cycling cells. We found that in the adult kidney, BrdU-retaining cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
274
2
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(299 citation statements)
references
References 45 publications
14
274
2
9
Order By: Relevance
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 93%
“…These cells demonstrated phenotypic plasticity, tubulogenic capacity, and integration capability into the developing kidney. Using a similar approach, another group identified label-retaining cells (LRCs) in the undamaged kidney using a much longer chase period [68]. This group reported that most of the LRCs were located in the interstitium of the renal papilla in the adult kidney, with very few cells being epithelial.…”
Section: Progenitors Isolated Based Upon Cellular Behaviourmentioning
confidence: 99%
“…In fact, spontaneous sphere formation by progenitor cells is not a phenomenon unique to progenitors isolated from the heart. Sphere formation also has been observed with neural, 30 retinal, 31 mammary, 32 kidney, 33 and prostate 34 progenitors and is thought to play a role in determining cell phenotype and survival. 35 We were highly successful using the cardiosphere method.…”
Section: Human Cardiosphere-derived Cardiac Stem Cellsmentioning
confidence: 99%
“…The identity of any renal stem cells has not been readily forthcoming. The renal papilla has been proposed as a niche area, based on the distribution of BrdU-labelled cells after a period of postnatal labelling in rodents, but the frequency of LRCs (40%) was far too high for them all to be stem cells [150]: nevertheless, LRCs disappeared after ischaemic injury and displayed clonal growth in vitro. Cells expressing Pax-2 and vimentin, with extensive clonogenic capacity in vitro and tubulogenic capacity in vivo, have been isolated from rat kidney; in one case they were CK-negative [151] and in another study came from the proximal tubule S3 segment [152].…”
Section: Kidneymentioning
confidence: 99%